Sociologia e Sociobiologia: autonomia vs. (socio)biologização da Sociologia - Alisson Magalhaes Soares (2009)
Since the 1970s the Sociobiology, a discipline borned from a newfocus in Biology (i.e. the gene as the main focus of natural selection, instead of group or species) engage in the study of social behavior of all animals, Humans included, and engage too in the study of how certain behaviors aroused evolutionarily. How it is the more general discipline about animals, sociobiology believes that can and must furnish a biological basis to the human sciences, humanities, ethics and epistemology. Such aim is followed today by the Evolutionary Psychology, an assumed daughter discipline of Sociobiology. This dissertation try to evaluate how well both disciplines understood the social sciences so criticized by themselves, and how well a sociobiological approachcan be useful or even crucial to the social sciences.